THE EFECT OF CLUSTERING APPROACH ON THE COMPETITIVE PERFORMANCE OF EXPORTING ENTERPRISES WITHIN THE SCOPE OF DEVELOPING INTERNATIONAL COMPETITION OF TURKISH EXPORTERS: AN APPLICATION IN CORUM (Third Sector Social Economic Review, 2020)
This study aims to investigate the effect of the cluster approach applied within the scope of UR-GE (Supporting the Development of International Competitiveness) on the export performance and competitiveness of exporting enterprises. In this study, the effects of companies producing ""agricultural food processing machines"" in Çorum province to national and international competition level, their effects on the intra-regional development level, the impact on export growth and export incentives on export performance were investigated and evaluated with UR-GE project.In this context, in-depth interviews were conducted with the companies producing ""Agricultural Food Processing Machines"" operating in Çorum by using the clustering approach. As a result of the study, it was found that the companies operating in the same sector and complementing each other tend to grow, develop and specialize in the direction of internationalization. At the same time, companies had the opportunity to compare themselves with their competitors in the global market and identified the deficiencies in their bodies. Thanks to this project, companies both had the opportunity to improve their visions and within competition  created a beneficial solidarity environment.
Keywords: Export Performance; Competition; Clustering; Government Supports